Ethnographic Analysis at General Practice Waiting Rooms: Implications for Postpartum Depression Detection and Treatment [Análisis Etnográfico en Salas de Espera de Centros de Salud Primaria: Implicancias Para la Detección y Tratamiento de la Depresión Posparto] - Magana-Frade, I; Martinez-Diaz, P (Sociedad Chilena de Psicologia Clinica, 2015)
In Chile, universal screening and treatment for postpartum depression has been implemented at a national level, however it remains under-detected and under-treated. To describe and analyze barriers to postpartum depression detection and treatment implied in maternal-infant health care production at general practice waiting rooms, an ethnographic study was carried out at six primary care clinics belonging to the Metropolitan Area of Santiago, Chile. Discourses and practices on maternity enacted at waiting room, reveals a conflicting condition for postpartum women, implying a differential overburden with domestic work and care tasks, demanding constant mobilization between formal and informal health care sources. The grade of integration between remunerated work and women s self-care is debated. © 2015 by Sociedad Chilena de Psicología Clínica.
Keywords: postpartum depression; cultural anthropology; health services accessibility; women s studies; nursing